HIV Risk Behaviours And Depression Among Female Drug Users (FDUs) In Malaysia - Mohd Noor, Normazaini; Singh, Darshan; B., Vicknasingam.; Narayanan, Suresh (2016)
Background: Female drug users (FDUs) dependent on amphetamine-type-stimulants (ATS) are predisposed to risky HIV behaviours and psychological problems. Objectives: This study aims to determine HIV risk behaviours and prevalence of depression among FDUs in Malaysia. Method: A total of 202 FDUs currently undergoing rehabilitation at an institutional rehabilitation centre in Bachok, Kelantan were surveyed. Respondents self-administered the behavioural survey questionnaire, and the Malay version Beck Depression Scale (BDS). Results: Most of the FDUs were Malays (87%, n=176/202), with a mean age of 29.47 years-old. Sixty-two percent (n=125/202) were above 26 years-old, two-third (67%, n=136/202) married, more than half (56%, n=114/202) have nine years of education, while 62% held employments prior to their detention. Majority (54%, n=109/202) self-reported to have used amphetamine-type-stimulants (ATS), while 46% (n=93/202) reported opiate + ATS use. Two-third (67%, n=136/202) reported living with a drug using male partner prior to their detention, 58% (n=118/202) were involved in illegal drug distribution activities, and only 10% (n=20/202) work as sex-workers. Seventy-seven percent (n=156/202) of the FDUs have no knowledge about female condom use. Results showed those who used only ATS and those who used opiate and ATS, were more likely to have irregular sex partners (OR: 1.3: 0.72-2.40: p<.371); to have never used condom with irregular sex partners (OR: 1.1: 0.39-2.91: p<.888); and used drugs during sex (OR: 1.4: 0.67-2.75: p<.393). Opiate + ATS users were more likely to inject (OR: 2.7: 1.31-5.46: p<.005); lend their injecting equipment (OR: 2.9: 1.09-7.56: p<.028); ask help during injection (OR: 2.6: 1.18-5.73: p<.015); and experience drug overdose (OR: 3.2: 1.69-5.97: p<.001), compared to those using only ATS. Notably, 75% (n=151/202) of the FDUs were found to be depress. Conclusion: Female drug users in Malaysia are vulnerable to HIV infections. Our findings suggest that proper harm reduction interventions targeting FDUs are needed.